Supplemental methods and association results from Kinship influences sperm whale social organization within, but generally not among, social units. - Christine M. Konrad; Shane Gero; Timothy Frasier; Hal Whitehead (2018)
Additional details on methods (social association indices, microsatellite genotyping and mtDNA haplotype sequencing; Tables S1 and S2) and on intra-social unit social dynamics (Tables S3 and S4, and Figure S1).